Dairy wastewater management in EU: Produced amounts, existing legislation, applied treatment processes and future challenges - Stasinakis, Athanasios S.; Charalambous, Panagiotis; Vyrides, Ioannis (My University, 2022)
Dairy industry consumes high water amounts and generates highly contaminated wastewater. EU-27 is the second largest milk producer and the main cheese exporter in the world. The main objectives of the current study was to estimate the amounts of dairy wastewater (DWW) that are produced annually in different EU countries and to present the relevant existing EU legislation. The main treatment practices currently applied as well as the future opportunities for sustainable DWW management were also discussed. According to the results a total amount of 192.5 × 106 m3 of DWW are annually produced in EU-27 countries, 49% of them are due to the production of cheeses, while 19%, 18% and 13% are due to the production of drinking milk, acidified milk and butterfat products, respectively. Six countries (Germany, France, Italy, Poland, Spain and Netherlands) contribute to the generation of more than 73% of DWW, while the annual per capita DWW production ranges between 36 L (Luxembourg) and 1441 L (Ireland). Since 2019, EU has established best available techniques (BAT) for the dairy industry in order to achieve efficient monitoring of the produced wastewater, reduced water consumption and increased resource efficiency. The main on-site treatment processes that are currently applied include in series wastewater pretreatment for the removal of fat and pH adjustment, anaerobic or/and aerobic biological processes for the decrease of organic loading and nutrients and use of membranes for the cases that recovered water is going to be reused. Limited information is so far available for the operational treatment cost of the different processes. Data originated from a large dairy industry in Cyprus showed an operational cost equal to 1.21 €/m3 of treated wastewater. The main future challenge for the dairy industry and water treatment sector is the adoption of novel processes aiming to DWW valorization under the frame of circular economy.
Keywords: Europe; Valorization; Treatment; Production; Milk processing wastewater